“Who’s been a good dog?”: owner perceptions and motivations for treat giving - White, G.A.; Ward, L.; Pink, C.; Craigon, J.; Millar, K.M. (Elsevier, 2016)
Complex relationships commonly exist between owners and their companion animals, particularly around feeding behaviour with an owner’s affection or love for their animal most pronounced through the provision of food. It is notable that the pet food market is experiencing strong year-on-year growth in sales of dog and cat treats. Recognising the impact of treat giving in pet nutrition, the objective of the study was to investigate owner attitudes and motivations towards feeding treats (shop bought and other) to their dogs. A researcher-mediated questionnaire consisting of both quantitative and qualitative questions was used to interview dog owners (n = 280) at two locations: an out-of-town retail park and a country park in the East Midlands. Owners almost unanimously viewed the word ‘treat’ within a nutritional context, as opposed to a new toy or other pleasure. The majority (96%) of owners interviewed reported feeding treats to their dog, with 69% feeding shop-bought treats on a daily basis. A wide range of treats was reportedly given by owners and the majority of owners interviewed fed multiple treat types. No association was found between owner age and frequency of shop-bought treats fed (P = 0.659) nor between owner age and frequency of food given to the dog from the owner’s plate (P = 0.083). A wide range of foods which would not be considered balanced for the animal’s nutritional requirements was viewed as a treat by some dog owners. A range of positive and negative views around the feeding of treats were expressed by dog owners, with some citing beneficial effects while others were clearly aware of the association between treat feeding and potential weight gain/obesity. Owner views included themes around positive reinforcement and responsibility but also reflected relational aspects of the human-animal bond. The results of the study show that treat giving is commonplace in feeding regimes and that treats are embedded in the feeding behaviour of many dog owners. However, the different views expressed around the motivations for, and feeding of, dog treats, reinforce the need to better understand owner psychology linked to this area, and the role this may play in the growing pet obesity epidemic.